Consumers' Preferences and Attitudes Toward Local Food Products. Issue 1 (2nd January 2016) - Aprile, Maria Carmela; Caputo, Vincenzina; Nayga, Rodolfo M.
Abstract: In recent years, consumers' interest in local food has significantly increased. Several studies in the agricultural economics and marketing literature have analyzed mainly consumers' preferences for local food products. In this study, we perform a consumer segmentation with regard to consumer behavior toward local food. We collected data from a survey conducted during summer 2010 in Naples, South Italy. Consumer segments were identified taking account of five aspects: (1) food consumption styles; (2) perception of local food; (3) purchasing motives; (4) perceived quality of local food; and (5) sociodemographic characteristics. They could be profiled as ethnocentric consumers, environmentalists, strict localists, and quality labeling oriented.